Effect of substituents at the C3 ́, C3 ́N, C10 and C2-meta-benzoate positions of taxane derivatives on their activity against resistant cancer cells - Daniel, Petr; Balušíková, Kamila; Truksa, Jaroslav; Černý, Jiří; Jaček, Martin; Jelínek, Michael; Mulenga, Mutale Jane Vobruba; Voráčová, Kateřina; Chen, Lei; Wei, Longfei; Sun, Yi; Ojima, Iwao; et al. (Toxicology and applied pharmacology, 2024)
We tested the effect of substituents at the (1) C3 ́, C3 ́N, (2) C10, and (3) C2-meta-benzoate positions of taxane derivatives on their activity against sensitive versus counterpart paclitaxel-resistant breast (MCF-7) and ovarian (SK-OV-3) cancer cells. We found that (1) non-aromatic groups at both C3 ́ and C3 ́N positions, when compared with phenyl groups at the same positions of a taxane derivative, significantly reduced the resistance of ABCB1 expressing MCF-7/PacR and SK-OV-3/PacR cancer cells. This is, at least in the case of the SB-T-1216 series, accompanied by an ineffective decrease of intracellular levels in MCF-7/PacR cells. The low binding affinity of SB-T-1216 in the ABCB1 binding cavity can elucidate these effects. (2) Cyclopropanecarbonyl group at the C10 position, when compared with the H atom, seems to increase the potency and capability of the derivative in overcoming paclitaxel resistance in both models. (3) Derivatives with fluorine and methyl substituents at the C2-meta-benzoate position were variously potent against sensitive and resistant cancer cells. All C2 derivatives were less capable of overcoming acquired resistance to paclitaxel in vitro than non-substituted analogs. Notably, fluorine derivatives SB-T-121205 and 121,206 were more potent against sensitive and resistant SK-OV-3 cells, and derivatives SB-T-121405 and 121,406 were more potent against sensitive and resistant MCF-7 cells. (4) The various structure-activity relationships of SB-T derivatives observed in two cell line models known to express ABCB1 favor their complex interaction not based solely on ABCB1.
Keywords: MCF-7 Cells; nádorové buněčné linie; paclitaxel; taxoidy; Breast Neoplasms; lidé; Taxoids; nádory vaječníků; Cell Line, Tumor; Antineoplastic Agents; MFC-7 buňky; ATP Binding Cassette Transporter, Subfamily B; chemorezistence; ženské pohlaví; protinádorové látky; vztahy mezi strukturou a aktivitou; Humans; nádory prsu; P-glykoproteiny; Benzoates; Paclitaxel; Female; benzoáty; Structure-Activity Relationship; Ovarian Neoplasms; Drug Resistance, Neoplasm